Diversity of Hepatocellular Carcinoma Clones Bearing Hematopoietic Malignancies‐Related Chromosomal Translocation. Issue 4 (April 2014) - Parent, Romain; Plissonnier, Marie‐Laure; Bancel, Brigitte; Liao, Wan‐Li; Rumin, Sylvie; Asaad, Remal; Till, Marianne; Sanlaville, Damien; Zoulim, Fabien; Trépo, Christian; Marion, Marie‐Jeanne
ABSTRACT Interpatient heterogeneity of hepatocellular carcinoma has been in‐depth addressed. Intrapatient heterogeneity is less known. Four clones were freshly isolated from an Edmondson grade I HCV‐associated hepatocellular carcinoma. Biochemical approaches, functional assays and cytogenetics were used. Albumin inducibility was uncoupled from canonical cytokeratin profiles, suggesting pathological combinations of hepatospecific and biliary markers. Poor differentiation and TGFβ's proproliferative effect on all clones were observed. TGFβ, Interferon α and doxorubicin sensitivity levels were found highly heterogeneous. Progenitor and stem cells markers OV6 and EpCAM were mutually exclusively expressed. All clones were CD44+, while none expressed CD90, CD133, or CD117. Three clones displayed a liver progenitor OV6+ phenotype, and were susceptible to hepatocytic differentiation, among which one fibroblastoid clone displayed intrahepatic parenchymal engraftment capability. A fourth clone, the less motile, displayed a cancer stem cell EpCAM+ phenotype, was essentially β‐catenin negative, and was as expected devoid of hepatocytic differentiation capability, yet the most sensitive to doxorubicin treatment. Cytogenetics evidenced in all clones a t(12;22)(p11;q11) translocation found in several myelodysplastic syndromes. All clones, that probably derive from EpCAM+ tumor cells, display aberrant E‐cadherin cytosolic localization. Because of their diverse pathophysiolocal features, these freshly isolated, low population doubling‐defined, HCC clones may provide novel opportunities to tackle HCC heterogeneity in a single patient background for therapy improvement purposes, especially regarding recently developed targeted strategies. J. Cell. Biochem. 115: 666–677, 2014. © 2013 Wiley Periodicals, Inc.